2011
DOI: 10.1121/1.3623747
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evidence of mixing in rooms using the free path temporal distribution

Abstract: The ergodic propriety of a room has strong effects on its reverberation. If the room is ergodic, the reverberation can be broken up in two steps: a deterministic process followed by a stochastic one. The late reverberation can be then modeled by a reverberation algorithm instead of more computationally consuming methods. In this study, the free path temporal distribution obtained by ray-tracing is used as an indicator of the room's mixing: the energetic average of the path lengths is computed at each time step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Several studies [8,16,20,21] have shown that the sound energy density in ar everberation experiment follows an exponential decay (t>0) in rooms with diffusely reflecting walls. Moreover, the slope of the decay is approximately the same at different positions in the room, though sometimes significantly different from the one predicted by Sabine or Eyring formula [20, p.139].…”
Section: Rooms With Diffusely Reflecting Boundaries and Diffuse Soundmentioning
confidence: 99%
“…Several studies [8,16,20,21] have shown that the sound energy density in ar everberation experiment follows an exponential decay (t>0) in rooms with diffusely reflecting walls. Moreover, the slope of the decay is approximately the same at different positions in the room, though sometimes significantly different from the one predicted by Sabine or Eyring formula [20, p.139].…”
Section: Rooms With Diffusely Reflecting Boundaries and Diffuse Soundmentioning
confidence: 99%
“…The results from the initial ray tracing procedure (1) are then employed to determine the diffused energy (4) and the remaining sound energy in the cavity at the transition time (5). Diffused sound energy is redirected into time bins that correspond to specific time windows before the transition time.…”
Section: Processmentioning
confidence: 99%
“…The impulse response can be obtained via testing or using predictions from numerical models. Such models are typically based on ray or beam tracing for the direct field and early reflections, and on statistical models for the late reflections which arrive after the so called transition time 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion model assumes that the energy is sufficiently scattered. In mixing rooms, the sound field becomes diffuse after about three mean-free time (a mean-free time is equal to λ/c, the time needed to travel a mean-free path) [30]. So the sound field ought to be sufficiently scattered at shorter times for diffusion model to be valid.…”
Section: Room Acoustics Criteriamentioning
confidence: 99%